Periods till psoriatic arthritis onset and diagnosis in Russian patients with moderate to severe psoriasis (according to psoriasis patient registry) - Alexey A. Kubanov; Elena V. Bogdanova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Background. Early detection of psoriatic arthritis in patients with psoriasis remains an unmet medical need. Early diagnosis and treatment initiation in patients with psoriatic arthritis decreases the risk of adverse patient outcomes and improves patients quality of life. Aims. To describe a period between psoriasis and psoriatic arthritis onset and a period between psoriatic arthritis onset and diagnosis in Russian patients with moderate to severe psoriasis. Materials and methods. Analysis of data from the psoriasis patient registry. Patients aged 18 years and older with an established diagnosis of psoriasis and psoriatic arthritis were included in the analysis. Noninclusion criteria: no data on psoriasis and/or psoriatic arthritis onset (for the period between psoriasis and psoriatic arthritis onset description); no data on psoriatic arthritis onset and/or diagnosis (for the period between psoriatic arthritis onset and diagnosis description). Results. Sample size for the descriptive characteristic of period between psoriasis and psoriatic arthritis onset was 891 patients; sample size for the descriptive characteristic of period between psoriatic arthritis onset and diagnosis was 849 patients. Psoriatic arthritis onset preceeded cutaneous manifestation of psoriasis in 2.5% of patients. Concurrent onset of cutaneous psoriasis and psoriatic arthritis (within one year) had 10.7% of patients. In 86.8% of patients, cutaneous manifestation of psoriasis preceded manifestation of psoriatic arthritis. Exclusively of patients with psoriatic arthritis developed before or concurrently with cutaneous manifestation of psoriasis, the mean duration of period between psoriasis and psoriatic arthritis onset was 13.7 10.3 years, the median [IQR] 12 [619] years. In 24% of patients psoriatic arthritis was diagnosed 1 year and more after its onset. The mean (SD) period from signs and|or symptoms onset till psoriatic arthritis diagnosis was 3.9 5.0 years; median [IQR] was 2 [14.5] years. Conclusions. A diagnostic delay in 24% Russian patients with psoriatic arthritis is one year or more. In this subgroup of patients the mean delay in diagnosis of psoriatic arthritis is about 4 years.